2017
DOI: 10.21141/pjp.2017.004
|View full text |Cite
|
Sign up to set email alerts
|

The Accuracy of Mean Neutrophil Volume Relative to Blood Culture for the Diagnosis of Sepsis: A Meta-analysis

Abstract: Background. Sepsis is difficult to diagnose clinically because the signs and symptoms are non-specific. Blood culture is the gold standard, but it has low sensitivity and it takes at least 24-48 hours before results are released. Cell population data such as mean neutrophil volume (MNV) has recently been shown to be significantly increased in septic patients both with high WBC and normal/low WBC count.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…The accuracy of the use of MNV may vary depending on age group, the nationality of patients as well as the model of analyzer used. 15 Table 3 displays the sensitivity and specificity in various studies nationally and internationally.…”
Section: Discussionmentioning
confidence: 99%
“…The accuracy of the use of MNV may vary depending on age group, the nationality of patients as well as the model of analyzer used. 15 Table 3 displays the sensitivity and specificity in various studies nationally and internationally.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in neutrophil ion and water homeostasis, frequently measured by changes in cell size, have been of increasing interest as diagnostic and prognostic markers in sepsis and other systemic inflammation conditions. A meta-analysis of the Area Under the Receiver Operating Characteristic Curve (AUROC) reported that a mean neutrophil volume of 0.87 (0.83–0.89) was an indicator for sepsis [ 12 ]. In accordance, alterations in neutrophil cell size occurred prior to organ dysfunction after severe injuries [ 16 ].…”
Section: Sepsis-induced Neutrophil Dysfunction and Its Correlationmentioning
confidence: 99%
“…Such a scenario can occur during the systemic inflammatory response in sepsis [ 3 , 5 , 6 , 7 ]. Recently, this neutrophil dysfunction has been increasingly associated with alterations in cellular size and intracellular cytosolic pH (henceforth referred to as “intracellular pH”), making an involvement of an ion–water disbalance likely [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%